Dinamika Kelisanan dan Keaksaraan dalam Produksi dan Resepsi Literatur Keagamaan Masyarakat Hadhrami di tanah Jambi - Wandi; M. Arif Musthofa (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2024)
This article focuses on the dynamics of the religious texts of the Hadhrami group that are circulated, used, influenced, and perceived by the Muslim community in Jambi. The literacy in the religious texts of the Hadhrami group will provide information regarding how the text is intertwined with the dynamics of local Islamic life, in this case the Jambi people. The question of this article is How are the dynamics of literacy in the religious texts of the Hadhrami community in Jambi? By analyzing the texts circulated and used by the Muslim community, coupled with participatory observation of the Hadhrami group in Jambi city for 3 months, starting from September, October, to November, it was found that the dynamics of literacy and literacy in the religious texts of the Hadhrami community in Jambi city, have changed a lot, such as the decline in translation and transliteration of Arabic texts. In addition, the presence of media technology has also influenced the dynamics of literacy in the last few decades.